Halide alloying and role of central atom on the structural and optical properties of decylammonium germanium 2D perovskites - Rossella Chiara; Gianluca Accorsi; Andrea Listorti; Mauro Coduri; Clarissa Coccia; Costanza Tedesco; Marta Morana; Lorenzo Malavasi (APL Energy, 2023)
We report here a novel series of halide alloyed Ge-containing 2D perovskites including decylammonium as organic spacer, namely DA2Ge(Br1−xIx)4. This system forms a continuous solid solution on the halide site with a modulation of the bandgap from 2.74 to 2.17 eV with a rapid decrease up to x = 0.5 followed by a plateau. Iodide-rich compositions show enhanced broad room temperature (RT) photoluminescence (PL) that narrows at low temperature with maximum quantum yields for mixed compositions. The replacement of Ge with Pb and Sn in DA2GeBr4 and DA2GeI4 provides a tuning of the bandgap in the whole visible spectrum with a marked blue-shift when lead is present and, opposite, a red-shift for Sn replacement. The RT PL progressively broadens moving from Pb to Sn and to Ge covering an emission range from 400 to 800 nm. Finally, the air stability of lead-free 2D perovskites of this work has been determined indicating its improvement by increasing the hardness of the halide.